THE METASTABLE OLIVINE WEDGE IN FAST SUBDUCTING SLABS: CONSTRAINTS FROM THERMO-KINETIC COUPLING - Daszler R.; Yuen D.A. (My University, 1996)
The effects of a strong non-linear thermo-kinetic coupling in the olivine-spinel transition are investigated with a 2D model for fast-subducting slabs. The thermo-kinetic coupling problem is solved in the Lagrangian framework by the differential algebraic method and by using experimental input parameters. Narrow regions with metastable olivine are found in fast and cold slabs down to the 660 km discontinuity, while the thermo-kinetic coupling reduces the depth and width of the zone where olivine and spinel coexist. In contrast to recent kinetic models, both latent heat release and heat diffusion place important constraints on the structure of the metastable wedge. Both processes trigger the ongoing phase transformation in the cold slab interior. A thermal instability over a short timescale (104-105 yr) can occur due to a positive thermo-kinetic feedback. This effect is enhanced at greater depths. The depth of the metastable wedge is found to be extremely sensitive to certain geophysical and thermodynamic parameters such as the lithospheric basal temperature, slab width and the activation energy for diffusion. Variations in these parameters within the experimental uncertainties can cause significant changes in the depth of the metastable wedge. Hence predictions about the exact position of the metastable olivine wedge are rather difficult. We propose that deep focus earthquakes may occur due to a thermal runaway caused by shear heating, while the thermal instability is enhanced by the latent heat release associated with the olivine-spinel phase transition.